2021
DOI: 10.1002/ecs2.3695
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the future of big sagebrush regeneration: challenges of projecting complex ecological processes

Abstract: Regeneration is an essential demographic step that affects plant population persistence, recovery after disturbances, and potential migration to track suitable climate conditions. Challenges of restoring big sagebrush (Artemisia tridentata) after disturbances including fire-invasive annual grass interactions exemplify the need to understand the complex regeneration processes of this long-lived, woody species that is widespread across the semiarid western U.S. Projected 21st century climate change is expected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Hotter and drier conditions in the future will likely increase fire risk throughout Wyoming shrublands, meaning it could be difficult to limit cheatgrass invasion if fires become widespread. Schlaepfer et al (2021) found a similar result in terms of sagebrush regeneration: regeneration will likely remain possible under a warming climate alone, but the fire‐cheatgrass interaction will likely limit sagebrush persistence. Nonetheless, our results corroborate those of Palmquist et al (2021) and Schlaepfer et al (2021) by suggesting that climate change alone should benefit, or at least not significantly disadvantage, sagebrush in Wyoming.…”
Section: Discussionmentioning
confidence: 82%
“…Hotter and drier conditions in the future will likely increase fire risk throughout Wyoming shrublands, meaning it could be difficult to limit cheatgrass invasion if fires become widespread. Schlaepfer et al (2021) found a similar result in terms of sagebrush regeneration: regeneration will likely remain possible under a warming climate alone, but the fire‐cheatgrass interaction will likely limit sagebrush persistence. Nonetheless, our results corroborate those of Palmquist et al (2021) and Schlaepfer et al (2021) by suggesting that climate change alone should benefit, or at least not significantly disadvantage, sagebrush in Wyoming.…”
Section: Discussionmentioning
confidence: 82%
“…In summary, the shift to bimodal seasonality may cause a shift toward R‐strategy grasses at the expense of perennial grasses and forbs and an increase in stress‐tolerant shrubs (S‐strategy plants), such as creosote ( Larrea tridentata ) and mesquite ( Prosopis spp. ), or small sclerophylls such as broom snakeweed ( Gutierrezia sarothrae ) (Bradford et al, 2020; McCormick et al, 2021; Moreno‐de las Heras et al, 2015; Schlaepfer et al, 2021). Unfortunately, many R‐strategy species are weedy and invasive, so these more “disturbed” or “stressful” habitats might transition to compositions with fewer native species (Grime, 1977, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used water-balance modeling and then employed K-means clustering to simplify the results for interpretation, but these decisions did not affect the robust projections for the expansion of bimodal seasonality. While our Thornthwaite-style water balance model neglects some mechanistic details considered by others (Bradford et al, 2020(Bradford et al, , 2021Schlaepfer et al, 2021), it has been used successfully in many applications where its moderate complexity makes it useful for interpreting relative differences across wide-geographical areas and diverse time periods and where model parameters for future time periods are not available, such as vegetation composition (Keim, 2010). Furthermore, more complex models also project increased future summer drought in the western United States (Bradford et al, 2020;Mankin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The socialecological system (SES) framework can help address wicked problems related to sustainability and resilience (Bodin 2017a;Ostrom 2009;Folke et al 2005). The SES framework has been a useful tool to assess rangelands (Roche 2021;Hruska et al 2017;Brunson 2012;Boyd and Svejcar 2009) such as the Sagebrush landscapesand decades of research have seen advances in characterizing interactions among biophysical (including ecological) components of the sagebrush system (Schlaepfer et al 2021;Chambers et al 2017;Davies et al 2011;Anderson and Inouye 2001;Connelly et al 2004). However, advancements in understanding the social and governance aspects or the coupled and interacting dimensions of the sagebrush SES and other CAS have lagged significantly behind.…”
Section: Introductionmentioning
confidence: 99%